Using accounting-based and loan-related information to estimate the cure probability of a defaulted company - Christian Lohmann; Thorsten Ohliger (European Financial Management, 2021)
The cure of a defaulted company has important implications for the estimation of the loss given default. In this study, we estimate the probability of a defaulted company being cured using data on a large international sample of defaulted companies. More specifically, we examine whether historic accounting information on a defaulted company and loan-related information are associated with that company's probability of being cured. The main finding of our analysis is that both accounting-based and loan-related independent variables increase the validity of cure prediction models.
Keywords: 650; accounting information; company cure; collateralization; cure probability; defaulted company; Global Credit Data